2021
DOI: 10.1038/s41598-021-03103-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of kinetin-induced death of Vicia faba ssp. minor root cortex cells

Abstract: Cell death (CD) may be induced by endogenous or exogenous factors and contributes to all the steps of plant development. This paper presents results related to the mechanism of CD regulation induced by kinetin (Kin) in the root cortex of Vicia faba ssp. minor. To explain the process, 6-(2-hydroxy-3-methylbenzylamino)purine (PI-55), adenine (Ad), 5′-amine-5′-deoxyadenosine (Ado) and N-(2-chloro-4-piridylo)-N′-phenylurea (CPPU) were applied to (i) block cytokinin receptors (CKs) and inhibit the activities of enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…A study on kinetin-induced cell death in the V. faba ssp. minor system (Kaźmierczak et al 2021 ) showed an increase of cytosolic calcium, which was accentuated by Ruthenium Red, suggesting that this calcium originates from internal stores, which is consistent with the current study. However, in the V. faba system, the elevated cytosolic calcium in presence of Ruthenium Red was accompanied by reduced cell death, which was also seen in the lace plant (Fraser et al 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A study on kinetin-induced cell death in the V. faba ssp. minor system (Kaźmierczak et al 2021 ) showed an increase of cytosolic calcium, which was accentuated by Ruthenium Red, suggesting that this calcium originates from internal stores, which is consistent with the current study. However, in the V. faba system, the elevated cytosolic calcium in presence of Ruthenium Red was accompanied by reduced cell death, which was also seen in the lace plant (Fraser et al 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Based on the ligand affinity patterns of different cytokinins, this receptor was also suggested to be involved in kinetin-induced cell death in V. faba ssp. minor roots (Kaźmierczak et al 2021 ). Generally, cytokinin receptors deploy signalling through mobile response regulators, and some of those connect with G-protein signalling (Wang et al 2017 ), which also would explain findings, where overexpression of a trimeric G-protein leads to a higher sensitivity against cytokinins (Plakidou-Dymock et al 1998 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of distinctive features (DNA fragmentation, the condensation of nuclear chromatin, and the release of cytochrome c from mitochondria) revealed a programmed character of induced cell death [60]. Kaźmierczak et al [63] describe the mechanism of kinetin-induced death of Vicia faba ssp. minor root cortex cells.…”
Section: Ck Inhibits Pollen Germination and Pollen Tube Growth In Sol...mentioning
confidence: 99%